Pengembangan LKPD Elektronik Berbasis Problem Based Learning pada Materi Elektrokimia - Meliana Fajri Nurkhasanah; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
Learning resources that are often used in learning only use limited print media and do not attract students' motivation, scientific attitude, and learning independence. For this reason, the right learning media is needed to improve it through electronic student worksheet media. This study aims to produce electronic student worksheet based on Problem-based Learning (PBL) on electrochemical material that is suitable for use in learning chemistry, determine characteristics, analyze practicality based on the assessment of high school chemistry teachers, and analyze responses and readability based on the assessment of high school students. This research used the Research and Development (R&D) research method with the 4D development model. The electronic student worksheet contains 4 learning activities and is equipped with pictures, audio, video, and declared feasible by chemistry learning experts. The results of the practicality test assessment by chemistry teachers obtained an average score of 94.4 out of a maximum score of 105 and an ideal percentage of 89.90% which is included in the ‘Very Good’ category. The results of the response test assessment and readability by students obtained an average score of 52.2 from a maximum score of 60, an ideal percentage of 87.50% which is included in the ‘Very Good’ category